Does nedocromil sodium have a steroid sparing effect in adult asthmatic patients requiring maintenance oral corticosteroids? - Goldin, J G (1988)
A randomised, double blind, placebo controlled trial of nedocromil sodium was undertaken to assess its corticosteroid sparing effect in 50 adults with asthma who had required an oral corticosteroid dose of (or equivalent to) at least 5 mg prednisolone a day continuously during the preceding year, in addition to inhaled beclomethasone dipropionate and bronchodilators. Patients having corticosteroids other than prednisolone were changed to prednisolone. A four week baseline period was followed by 20 weeks of inhaled nedocromil sodium (16 mg daily) or placebo. After four weeks of the treatment phase an attempt was made to reduce the oral prednisolone maintenance dose by 2.5 mg a fortnight until a dose of 5 mg daily was reached and thereafter by 1 mg a fortnight, provided that there was no significant clinical deterioration as judged by clinic assessments and daily diary cards. Of 50 patients recruited, 47 entered the treatment phase (age range 16-64 years), 24 receiving nedocromil sodium and 23 placebo. The total steroid reduction achieved was 2.5 mg in the nedocromil group and 3 mg in the placebo group, which did not differ significantly. There was no significant change in symptoms, lung function or inhaler use in either group during the study. The number of patient requiring short term upward adjustment of booster doses of oral prednisolone for exacerbations of asthma was similar in the two groups (26 with placebo, 28 with nedocromil). Thus nedocromil sodium does not appear to provide an oral corticosteroid sparing effect in chronic steroid dependent asthma.